Effects of a Parenting Preparation Course on Preferred Mode of Delivery, Fear of Childbirth, and Perception of Traumatic Childbirth in Midwifery Students - Ezgi ŞAHİN; Saadet YAZICI (Golestan University of Medical Sciences, 2022)
Background: The research was carried out to examine the effect of a parenting preparation course given to midwifery students during an academic semester on the preferred mode of delivery, fear of childbirth, and traumatic birth perception. Methods: This was a quasi-experimental study with a pretest-posttest design that included 47 second-year students enrolled in the parenting preparation course. Students took the parenthood preparation course, 2 hours a week, for 14 weeks. Data were collected using a descriptive information form, the pre-pregnancy fear of birth scale, and the perception of traumatic birth scale. Paired t-test and chi-square test were used to evaluate intragroup and intergroup differences. The data were analyzed using SPSS 22.0 software at a statistical significance of 0.05. Results: The mean age of the students was 20.13±0.67 years. The mean score of pre-pregnancy fear of childbirth was 40.46±9.37 in the pretest and 23.61±6.79 in the posttest. In addition, the mean score of traumatic childbirth perception decreased from 77.34±25.15 in the pretest to 39.44±13.78 in the posttest. The number of students who preferred cesarean section decreased significantly, while the number of students who preferred vaginal delivery increased after the preparation course. Conclusion: Parenting preparation classes can contribute to the reduction of fear of childbirth and the perception of traumatic childbirth in women.